Increased spindle density correlates with sleep continuity improvements following an eight‐week course of a melatonin agonist in people with depression: A proof‐of‐concept study with agomelatine. (28th June 2021) - Porteous, Meggan; Fogel, Stuart; Ray, Laura; Hickie, Ian B.; Carpenter, Joanne S.; Louati, Khaoula; Robillard, Rebecca
Abstract: Sleep fragmentation and reductions in sleep spindles have been observed in individuals with depression. Sleep spindles are known to play a protective role for sleep, and there are indications that melatonin agents can enhance spindles in healthy people. Whether agomelatine, a melatonin agonist indicated for the treatment of depression, may increase spindle density sufficiently to impact sleep continuity in people with depression remains unknown. This proof‐of‐concept study investigated changes in spindles following agomelatine intake in young adults with depression and assessed how they may relate to potential changes in sleep continuity and depressive symptoms. This study was based on an open‐label design. Fifteen participants between 17 and 28 years of age (mean = 22.2; standard deviation [ SD ] = 3.4) with a diagnosis of a depressive disorder underwent polysomnography before and after an intervention including a 1 hr psychoeducation session centered on sleep and circadian rhythms, and an 8‐week course of agomelatine (25–50 mg) with a guided sleep phase advance. Fast spindle density significantly increased from pre‐ to post‐intervention. This increase in spindle density significantly correlated with a reduction in wake after sleep onset, and a similar trend was found with increased sleep efficiency. There was no significant correlation between spindle parameters and depressive symptoms. These findings suggest that agomelatine may contribute to enhanced sleep consolidation, possibly in part through the modulation of spindle production. This should be confirmed by larger randomized control trials. Abstract : Whether agomelatine, a melatonin agonist indicated for the treatment of depression, may increase spindle density sufficiently to impact sleep continuity in people with depression remains unknown. Results suggest that fast spindle density significantly increased from pre‐ to post‐intervention, especially during the first quarter of the night, and that the increase in spindles correlated with improved sleep consolidation.